Intravenous administration of granulocyte colony-stimulating factor for treating neuropathic pain associated with compression myelopathy: a phase I and IIa clinical trial - Kato, Kei (Springer-Verlag, 2012)
OBJECTIVE: To confirm the feasibility and safety of granulocyte colony-stimulating factor (G-CSF) for treating spinal neuropathic pain associated with compression myelopathy, we have initiated an open-label single-center prospective clinical trial. METHODS: Between January 2009 and February 2011, 17 patients were accrued and were divided into two groups. One group included 7 patients who complained of pain associated with worsening symptoms of myelopathy (progressing myelopathy-related pain group). The other group included 10 patients who complained of pain that persisted after surgery for compression myelopathy (post-operative persistent pain group). All patients underwent intravenous administration of G-CSF (10 μg/kg/day) for 5 consecutive days. Pain severity was evaluated using a visual analog scale (VAS) before and after G-CSF administration. RESULTS: In 14 of the 17 patients, pain was relieved within several days after G-CSF administration. Pain disappeared completely in 3 patients. In the progressing myelopathy-related pain group, the mean VAS score was 71.4/100 before G-CSF administration, and decreased to 35.9/100 at 1 week after G-CSF administration (p < 0.05). In the post-operative persistent pain group, the mean VAS score was 72.0/100 before G-CSF administration, and decreased to 51.7/100 at 1 week after G-CSF administration (p < 0.05). No severe adverse events occurred during or after G-CSF administration. CONCLUSIONS: The present results provide us with the possibility that G-CSF has a pain-relieving effect for neuropathic pain in patients with compression myelopathy.